Dynamic model of choosing an external funding instrument - Honková Irena (My University, 2015)
Making a decision about using a specific funding source is one of the most important tasks of financial management. The utilization of external sources features numerous advantages yet staying aware of diverse funding options is not easy for financial managers. Today it is crucial to quickly identify an optimum possibility and to make sure that all relevant criteria have been considered and no variant has been omitted. Over the long term it is also necessary to consider the category of time as changes made today do not affect only the current variables but they also have a significant impact on the future. This article aims to identify the most suitable model of choosing external funding sources that would describe the dynamics involved. The first part of the paper considers the theoretical background of external funding instrument and of decision criteria. The making of financial decisions is a process consisted of weighing the most suitable variants, selecting the best variant, and controlling the implementation of accepted proposals. The second part analyses results of the research - decisive weights of the criteria. Then it is created the model of the principal criteria Weighted Average Cost of Capital (Dynamic model WACC). Finally it is created the Dynamic Model of Choosing an External Funding Instrument. The created decision-making model facilitates the modeling of changes in time because it is crucial to know what future consequences lies in decisions made the contemporary turbulent world. Each variant features possible negative and positive changes of varying extent. The possibility to simulate these changes can illustrate an optimal variant to a decision-maker.
Dynamický model výběru externího nástroje financování
Keywords: Dynamic model; external financial source; Dynamický model; externí nástroje financování